Do Continuing Medical Education (CME) Events Cover the Content Physicians Want to Know? A Content Analysis of CME Offerings. (2015) - Bjerre, Lise M.; Paterson, Nicholas R.; McGowan, Jessie; Hogg, William; Campbell, Craig; Viner, Gary; Archibald, Douglas
Abstract : Introduction: : The purpose of this study is to assess whether annual refresher session offerings match the needs of physicians by coding and comparing session syllabi to physician questions collected electronically at the point of care. Methods: : Thirteen syllabi from annual refresher continuing medical education (CME) events offered to family physicians in Canada were collected and their session titles and descriptions entered into a database. Titles and descriptions were coded using the International Classification for Primary Care version 2 (ICPC‐2). Titles and descriptions were further coded depending on whether the sessions involved a drug treatment/medication component. Syllabi content was compared to previously determined questions asked by physicians at the point of care. Results: : Of the original 701 session titles, 625 (89.2%) were suitable for analysis. CME sessions focused on musculoskeletal, digestive, skin, urologic, and general categories were underrepresented in comparison to point‐of‐care questions. The reverse was true for the psychological/mental health category. Discussion: : Differences between questions asked by physicians at the point of care and the content of contemporaneous CME refresher courses can be analyzed to identify gaps in CME offerings. This knowledge could be used to develop CME curricula and highlight areas of need for inclusion in refresher courses.